Emission benefits from the use of n-butanol blends in a Euro 6 diesel engine. (December 2018) - Lapuerta, Magín; Hernández, Juan José; Rodríguez-Fernández, José; Barba, Javier; Ramos, Angel; Fernández-Rodríguez, David
Tests with diesel/n-butanol blends (up to 20% by volume) were carried out in a Euro 6 engine following the New European Driving Cycle in a test bench. No decrease in engine efficiency was observed when n-butanol is used and fuel consumption increased proportionally to its lower heating value. Regarding emissions, total hydrocarbon and carbon monoxide increased when n-butanol is used. On the other hand, the use of n-butanol reduces the particle emissions down to a minimum value (for around 16% of n-butanol content) and then increases particle emissions again. This was observed in both mass and particle number. This trend occurs as a consequence of the compromise between the increase in oxygen content, which inhibits soot formation, and the increase in hydrocarbon emissions, especially under cold-engine conditions, which promotes liquid nucleation. Finally, NOX emissions remained unchanged as a consequence of the compensation between larger ignition delays and shorter combustion durations.